Thermal Performance Analysis And Characterization For Mobile Radio - Chee, Jiunn Shyong (2013)
Steady natural convection flow field and its heat transfer of a mobile radio are very complex and three dimensional. Accurate and reliable numerical solution for low speed (at the magnitude of 1 x 10-1 m/s), transitional flow induced by the interaction between buoyancy force and gravity is yet a challenge on many commercially available computational fluid dynamic (CFD) codes, as these CFD codes mainly developed for solving forced convection heat transfer analysis. In this study, the appropriate boundary conditions, turbulence model, external volume and meshing methods that contribute to a reliable CFD heat transfer prediction of a mobile radio were identified by utilizing CFDesign, a commercial finite element method CFD tool. Prior to carry out a thermal simulation of natural convection on a mobile radio, efforts to validate the prediction accuracy of CFDesign for different turbulence models, which are zero-equation mixing-length, two-equation κ-ε and Low-Reynolds κ-ε were carried using a simple rectangular square enclosure with heat source located centrally on the bottom surface. Isotherm results obtained are correlated with results published by Calcagni, Marsili et al. (2005), predicted by means of Fluent, a finite volume method code, and also results from Aydin and Yang (2000) by utilizing finite difference method code. The purpose of this prediction accuracy validation is to identify the most suitable turbulence model that deliver realistic temperature distribution and flow field of natural convection heat transfer CFD simulation in CFDesign.